Age-related hearing loss and its potential drug candidates: a systematic review - Shiyu Hu; Qingru Sun; Fei Xu; Ninghua Jiang; Jianli Gao (BMC, 2023)
Abstract Background Age-related hearing loss (ARHL) is one of the main illnesses afflicting the aged population and has a significant negative impact on society, economy, and health. However, there is presently no appropriate therapeutic treatment of ARHL due to the absence of comprehensive trials. Objectives The goal of this review is to systematically evaluate and analyze recent statistics on the pathologic classifications, risk factors, treatment strategies, and drug candidates of ARHL, including that from traditional Chinese medicine (TCM), to provide potential new approaches for preventing and treating ARHL. Methods Literature related to ARHL was conducted in databases such as PubMed, WOS, China National Knowledge Infrastructure (CNKI), and Wanfang from the establishment of the database to Jan, 2023. The pathology, causal factor, pathophysiological mechanism, treatment strategy, and the drug candidate of ARHL were extracted and pooled for synthesis. Results Many hypotheses about the etiology of ARHL are based on genetic and environmental elements. Most of the current research on the pathology of ARHL focuses on oxidative damage, mitochondrial dysfunction, inflammation, cochlear blood flow, ion homeostasis, etc. In TCM, herbs belonging to the kidney, lung, and liver meridians exhibit good hearing protection. Seven herbs belonging to the kidney meridian, 9 belonging to the lung meridian, and 4 belonging to the liver meridian were ultimately retrieved in this review, such as Polygonum multiflorum Thunb., Panax ginseng C.A. Mey, and Pueraria lobata (Willd.) Ohwi. Their active compounds, 2,3,4',5-Tetrahydroxystilbene-2-O-D-glucoside, ginsenoside Rb1, and puerarin, may act as the molecular substance for their anti-ARHL efficacy, and show anti-oxidative, neuroprotective, anti-inflammatory, anti-apoptotic, or mitochondrial protective effects. Conclusion Anti-oxidants, modulators of mitochondrial function, anti-inflammation agents, vasodilators, K+ channel openers, Ca2+ channel blockers, JNK inhibitors, and nerve growth factors/neurotrophic factors all contribute to hearing protection, and herbs are an important source of potential anti-ARHL drugs.